PENGARUH ETOS KERJA DAN ETIKA TERHADAP KARIER SESEORANG DI DUNIA KERJA MODERN - Sandra Dwi Rapianti; Riri Amrilia; Mutiara Yulisma; Fika Febriani (PT. Hasba Edukasi Mandiri, 2025)
This study aims to understand the influence of work ethic and ethics on career development in the modern workplace. A strong work ethic and the application of professional ethics are two important factors in determining career success in today's era of global competition. The method used is a qualitative descriptive approach with analysis of secondary data obtained from various previous sources such as scientific journals, books, and professional organization reports. The results of the study indicate that a strong work ethic, such as discipline, responsibility, and enthusiasm for achievement, along with the application of good ethics such as honesty and integrity, have a positive impact on professional reputation and career advancement opportunities. This study confirms that career success is determined not only by technical competence but also by moral quality and work ethic. Furthermore, a good work ethic helps strengthen trust and a person's professional reputation in the workplace. Thus, it can be concluded that work ethic and ethics play a significant role in shaping a successful, sustainable, and integrity-based career in the modern workplace.